Comparison of 7-site skinfold measurement and dual-energy X-ray absorptiometry for estimating body fat percentage and regional adiposity in Taiwanese diabetic patients. - Feng-Chih Kuo (PLoS ONE, 2020)
Obesity and regional adiposity are important risk factors for cardiometabolic disorders. The aim of this study is to compare 7-site skinfold (SF) measurement to dual-energy x-ray absorptiometry (DXA) as the reference method for estimating body fat percentage (BF%) and regional adiposity in diabetic outpatients. A total of 59 diabetic patients (36 females and 23 males) aged 28.5-78 years (median 67.7 years) with BMI 18.8-40.6 kg/m2 (median: 25.5 kg/m2) were enrolled. 7-site skinfold measurement and DXA were performed at the same visit day and biochemistry data were collected. Our results demonstrate the BF% calculated via Jackson & Pollock 7-site skinfold equation presents a strong correlation (r = 0.672, p < 0.001 in females; r = 0.885, p < 0.001 in males) with that measured by DXA, but the means of BF% between these two methods are significantly different in both sexes (paired t-test, p < 0.001). The Bland-Altman analysis showed the mean differences (DXA-SF) of BF% were positive for female (8.74%) and male (7.22%), suggesting Jackson & Pollock 7-site skinfold equation tends to underestimate the BF%. Besides, regional SF thicknesses of 7-site skinfold measurement were significantly correlated with the matched regional adiposity quantified by DXA. Furthermore, truncal and android SF thicknesses were notably positively correlated with several cardiometabolic risk factors in gender-specific manner. Our data indicate the 7-site skinfold measurement is not an interchangeable method for precisely measuring BF%, but might be practical for evaluating the cardiometabolic risks in Taiwanese diabetic outpatients.